Modeling and Control of Sustainable Power Systems Towards Smarter and Greener Electric Grids - Wang, Lingfeng; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The concept of the smart grid promises the world an efficient and intelligent approach of managing energy production, transportation, and consumption by incorporating intelligence, efficiency, and optimality into the power grid. Both energy providers and consumers can take advantage of the convenience, reliability, and energy savings achieved by real-time and intelligent energy management. To this end, the current power grid is experiencing drastic changes and upgrades. For instance, more significant green energy resources such as wind power and solar power are being integrated into the power grid, and higher energy storage capacity is being installed in order to mitigate the intermittency issues brought about by the variable energy resources. At the same time, novel power electronics technologies and operating strategies are being invented and adopted. For instance, Flexible AC transmission systems and phasor measurement units are two promising technologies for improving the power system reliability and power quality. Demand side management will enable the customers to manage the power loads in an active fashion. As a result, modeling and control of modern power grids pose great challenges due to the adoption of new smart grid technologies. In this book, chapters regarding representative applications of smart grid technologies written by world-renowned experts are included, which explain in detail various innovative modeling and control methods.
From the content: Real Time Modeling and Control of Smart Grid Systems -- Smart Grids Operation with Distributed Generation and Demand Side Management -- Active and reactive power control of grid connected distributed generation systems -- Modeling and Control for Islanding Operation of Active Distribution Systems -- Control Methods for Grid Side Converters under Unbalanced Operating Conditions in Wind Power Applications.
Keywords: Engineering; Production of electric energy or power; Renewable energy sources; Engineering; Renewable and Green Energy; Control; Renewable and Green Energy; Power Electronics, Electrical Machines and Networks